CONTRIBUTIONS FROM GLACIALLY DERIVED SEDIMENT TO THE GLOBAL IRON (OXYHYDR)OXIDE CYCLE: IMPLICATIONS FOR IRON DELIVERY TO THE OCEANS - Raiswell R.; Benning L.G.; Tranter M.; Siegert M.; De'ath R.; Payne T.; Huybrechts P. (My University, 2006)
Estimates of glacial sediment delivery to the oceans have been derived from fluxes of meltwater runoff and iceberg calving, and their sediment loads. The combined total (2900 Tg yr-1) of the suspended sediment load in meltwaters (1400 Tg yr-1) and the sediment delivered by icebergs (1500 Tg yr-1) are within the range of earlier estimates. High-resolution microscopic observations show that suspended sediments from glacial meltwaters, supraglacial, and proglacial sediments, and sediments in basal ice, from Arctic, Alpine, and Antarctic locations all contain iron (oxyhydr)oxide nanoparticles, which are poorly crystalline, typically ~5 nm in diameter, and which occur as single grains or aggregates that may be isolated or attached to sediment grains. Nanoparticles with these characteristics are potentially bioavailable. A global model comparing the sources and sinks of iron present as (oxyhydr)oxides indicates that sediment delivered by icebergs is a significant source of iron to the open oceans, beyond the continental shelf. Iceberg delivery of sediment containing iron as (oxyhydr)oxides during the Last Glacial Maximum may have been sufficient to fertilise the increase in oceanic productivity required to drawdown atmospheric CO2 to the levels observed in ice cores. © 2006 Elsevier Inc. All rights reserved.